Fatty acid and tocochromanol patterns of Turkish pines - Bagci, E; Karaagaçli, Y (Polska Akad Nauk, Polish Acad Sciences, Pas Branch Cracow, 2004)
The plant family Pinaceae is known to produce a set of unusual fatty acids in the seed oils. In Turkey it has been less studied in respect to the fatty acid and tocochromanol (tocopherols and tocotrienols) composition of the seed oils, particularly in terms of chemotaxonomy. This study examined the fatty acid, tocopherol, tocotrienol and plastochromanol-8 content of Pinus L. taxa naturally growing in Turkey (Pinus nigra subsp. pallasiana, P. nigra subsp. pallasiana var. pyramidata, P. halepensis, P. sylvestris, P. pinea, P. brutia, P. radiata, P. pinaster). The fatty acids (oleic, linoleic, alpha-linolenic, Delta5-taxoleic, pinolenic and coniferonic acid) and tocochromanols are valuable components of Pinus seed oils. in the family Pinaceae. Unsaturated fatty acid comprises similar to90% of the seed oil. While gamma-tocopherol was found to be the largest component of all Pinus seed oil, P-tocotrienol was not found at all. Total tocopherols in the studied taxa was much higher than total tocotrienols. The distribution of fatty acid and tocochromanol patterns in the genus Pinus is discussed, and in particular the presence of Delta5-UPIFA acids such as taxoleic and pinolenic acids, as well as common and distinguishing features that may contribute to knowledge about the taxonomy and phylogeny of pines.
Keywords: Pinaceae; Pinus; fatty acid; tocochromanol chemotaxonomy; phylogeny